FORMATION AND DEVELOPMENT OF ART EDUCATION IN KATERINOSLAV (DNIPROPETROVSK) END OF XVIII - MID-XIX CENTURY - O.M. Svitlychna (Academy of Cognitive and Natural Sciences, 2022)
The article deals with the peculiarities offoundation and development of the artics tic education in Katerinoslav (Dnepropetrovsk) from the end of the XVIII till the middle of the XIX century.